Palm‐Sized Ag+ Ion Emission Gun Operated at Room Temperature in Non‐Vacuum Atmosphere. Issue 9 (24th May 2018) - Daiko, Yusuke; Segawa, Kyohei; Machida, Kodai; Imataka, Hiroaki; Honda, Sawao; Iwamoto, Yuji
Abstract : Ion implantation is an effective method for changing surface properties and inducing various functionalities. However, a high vacuum is generally necessary for ion implantation, which limits the range of applications. Here, we describe a palm‐sized Ag + ion emission gun produced using a solid electrolyte. AgI–Ag2 O–B2 O3 glass, known as a super‐ion‐conducting glass, has a Ag + ion conductivity higher than 5 × 10 −3 S cm −1 at room temperature. In addition, the melted glass has suitable viscous flow, and a sharp glass‐fiber emitter with a pyramid‐like apex can be obtained. Ag + ion emission is observed from the tip of the glass fiber at accelerating voltages corresponding to electric fields above 20 kV cm −1, even at room temperature in a non‐vacuum atmosphere. Ag nanoparticles of size 50–350 nm are precipitated on a Si target substrate. Other glass components such as boron and iodine are not detected. Electrochemical quartz crystal microbalance (EQCM) measurements show that the mass of Ag nanoparticles estimated from the emission current using Faraday's law of electrolysis is in good agreement with that estimated from the QCM frequency shift. Abstract : A palm‐sized Ag + ion emission gun is developed using high Ag + ‐ion‐conducting AgI–Ag2 O–B2 O3 glass. A sharpened glass‐fiber tip with a triangular pyramid‐like apex is crucial for Ag + ion emission in a non‐vacuum atmosphere.